MICROSTRUCTURAL EVOLUTION IN HEAT-TREATED CAST IRONS - Rana, Anwar Manzoor; Khan, Abdul Faheem; Amjad, Sohail; Abbas, Tahir (Journal of Research (Science), 2001)
Samples of two different compositions of cast irons were annealed and quenched at 800 °C and tempered at 600 °C for 30 minutes. The Rockwell hardness (HRC) of the annealed samples was found to decrease. However, HRC values were found to increase for both quenched and tempered samples. It has been investigated that the increased hardness of quenched sample was due to formation of martensitic needles.